Release of an HtrA-Like Protease from the Cell Surface of Thermophilic Brevibacillus sp. WF146 via Substrate-Induced Autoprocessing of the N-terminal Membrane Anchor - Zhu, Fengtao; Yang, Xing; Wu, Yan; Wang, Yasi; Tang, Xiao-Feng; Tang, Bing (Frontiers in Microbiology, 2017)
High-temperature requirement A (HtrA)-like proteases participate in protein quality control in prokaryotes and eukaryotes by degrading damaged proteins; however, little is known about HtrAs produced by thermophiles. HtrAw is an HtrA-like protease of thermophilic Brevibacillus sp. WF146. The intact form of HtrAw (iHtrAw) consisting of a transmembrane segment (TMS)-containing N-terminal domain, a trypsin-like protease domain, and a C-terminal PDZ domain was produced in Escherichia coli. Purified iHtrAw itself is unable to cleave the N-terminal domain, but requires protein substrates to autoprocess the N-terminal domain intermolecularly, yielding a short form (sHtrAw). Mutation at the substrate-binding site in the PDZ domain affects the conversion of iHtrAw to sHtrAw. Deletion analysis revealed that the N-terminal domain is not necessary for enzyme folding, activity, and thermostability. Compared with other known HtrAs, HtrAw contains an additional Ca2+-binding Dx[DN]xDG motif important for enzyme stability and/or activity. When produced in an htrA/htrB double deletion mutant of Bacillus subtilis, iHtrAw localized predominantly to the cell pellet, and the amount of sHtrAw in the culture supernatant increased at elevated temperatures. Moreover, HtrAw increased the heat resistance of the B. subtilis mutant. In strain WF146, HtrAw exists in both a cell-associated intact form and a cell-free short form; an increase in growth temperature enhanced HtrAw production and the amount of cell-free short form. Release of the short form of HtrAw from the membrane may have the advantage of allowing the enzyme to freely access and degrade damaged proteins surrounding the bacterium living at high temperatures.